Making music as home-making: Bosnian refugee music and collaboration in Post-Yugoslav Slovenia - Bartulović, Alenka (Muzikološki zbornik, 2019)
This article explores some of the musical practices of Bosnian refugees in post-Yugoslav Slovenia in the mid-1990s and aims to improve understandin-gs of music in transit and in precarious times. In particular, the article traces the effects of common Yugoslav history on the popularisation of Sevdali-nka in Slovenia and the efforts of refugee and local musicians to make a new home together after the breakup of Yugoslavia.
Keywords: begunci; Bosna in Hercegovina; Bosnia-Herzegovina; glasbeno sodelovanje; home-making; making music; musical cooperation; postjugoslovanska Slovenija; post-Yugoslav Slovenia; refugees; ustvarjanje doma; ustvarjanje glasbe